2022
DOI: 10.1002/tox.23709
|View full text |Cite
|
Sign up to set email alerts
|

EF‐24 inhibits TPA‐induced cellular migration and MMP‐9 expression through the p38 signaling pathway in cervical cancer cells

Abstract: Diphenyl difluoroketone (EF-24), a synthetic curcumin analog, has enhanced bioavailability over curcumin. EF-24 acts more powerful bioactivity for anti-inflammatory and anti-cancer activity. However, the effects and mechanism of EF-24 on cervical cancer has not been fully investigated. Herein, this study evaluated the effects of EF-24 on TPA-induced cellular migration of cervical cancer. The results showed that EF-24 substantially reduced the cellular migration and cellular invasion of the HeLa and SiHa cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…In this work, we intended to characterize OTUB2 expression and function in CC and explore its relation to RBM15 and AKT/mTOR signaling pathway. Our findings showed that RBM15-mediated m 6 A modification led to OTUB2 upregulation in CC cells, thereby promoting malignant phenotypes of CC cells via activation of the AKT/mTOR signaling. Taken together, this study uncovered a novel regulatory molecular mechanism of OTUB2 in CC in vitro, providing the potential of OTUB2 as a therapeutic target for CC.…”
mentioning
confidence: 65%
See 4 more Smart Citations
“…In this work, we intended to characterize OTUB2 expression and function in CC and explore its relation to RBM15 and AKT/mTOR signaling pathway. Our findings showed that RBM15-mediated m 6 A modification led to OTUB2 upregulation in CC cells, thereby promoting malignant phenotypes of CC cells via activation of the AKT/mTOR signaling. Taken together, this study uncovered a novel regulatory molecular mechanism of OTUB2 in CC in vitro, providing the potential of OTUB2 as a therapeutic target for CC.…”
mentioning
confidence: 65%
“…N6-methyladenosine (m 6 A) modification of messenger RNAs (mRNAs) is highly conserved in mammals 19 and has huge impacts on gene regulation. 20 Recent studies have demonstrated the important role of m 6 A RNA methylation in human cancers, including CC. 21 The m 6 A methylation is a reversible process involving RNA methyltransferases ("writers"), RNA demethylases ("erasers"), and RNA-binding proteins ("readers").…”
mentioning
confidence: 99%
See 3 more Smart Citations